Abnormal uterine bleeding in perimenopausal women: correlating PALM-COEIN classification with histopathological findings - Thakur, Archana; Singh, Shakun; Chaudhary, Rachna; Modi, Prapti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: The most prevalent menstruation issue during perimenopause is abnormal uterine bleeding (AUB). A categorization system (PALM-COEIN) for the etiology of AUB in non-gravid women has been created by the International Federation of Gynecology and Obstetrics working group on menstrual disorders. Aims and objectives were to analyse the structural (PALM) and functional (COEIN) components of the PALM-COEIN system of AUB in perimenopausal women and correlate it histopathologically. Methods: This prospective analytical study was conducted over 18 months at LLRM Medical College, Meerut, involving 172 perimenopausal women aged 40-49 years presenting with AUB. Ultrasonography was done and etiology of AUB was ruled out by PALM–COEIN classification and then was correlated with histopathology findings. Results: Heavy and prolonged bleeding was the most common complaint (26.1%). Ultrasonographic (USG) findings revealed adenomyosis in 26.7% of cases, followed by fibroids (22.0%) and thickened endometrium (16.8%). Histopathological examination identified proliferative phase endometrium as the most prevalent finding (31.98%), followed by simple cystic hyperplasia (14.53%) and benign polyps (13.95%). A significant correlation was observed between USG and histopathological findings (p<0.001). Conclusions: This study findings emphasize necessity for integrating clinical assessment, imaging, and histopathological evaluation to accurately identify underlying causes of AUB and guide appropriate management strategies.